Influence of copolymer composition of polyestercarbonate on miscibility with poly(butylene terephthalate) - Lee, SS; Jeong, HM; Jho, JY; Ahn, TO (WILEY, 2000)
Blends of poly(butylene terephthalate) (PBT) and polyestercarbonate (PEC), copolyesters consisting of polycarbonate (Pe) and polyarylate (PAr), have been studied by thermal analysis to determine miscibility. The PET blends with PAr and PEC containing 30 wt % of carbonate unit or less appeared to be miscible, and the tendency for stable single-phase was observed to decrease as the content of carbonate unit in PEC copolymer increased. As determined with the crystalline phase behavior, the miscibility of PEC with PET appeared to have a maximum around 10 similar to 30 wt % of carbonate content in PEC copolymer, and this result was attributed to the internal repulsion effect between ester and carbonate repeating units in PEC copolymer. (C) 2000 John Wiley & Sons, Inc.
Keywords: POLY(2,6-DIMETHYL-1,4-PHENYLENE OXIDE); POLYARYLATE BLENDS; BPA POLYCARBONATE; PHASE-BEHAVIOR; POLYSTYRENE; MORPHOLOGY